Sherlock Holmes and the Rune Stone Mystery - Millett, Larry, 1947- (Book collections on Project MUSE., 2012)
Sherlock Holmes is bored between cases at 221B Baker Street. So when King Oskar II of Sweden-who has heard of the discovery of the Kensington Rune Stone by a farmer in Minnesota-asks to engage his services, Holmes jumps at the chance to decipher the runes and determine whether the find is real or a hoax. With Dr. John H. Watson by his side, faithfully recording every detail, Holmes makes his way to Minnesota for a third time. But, in the first of many strange and unfortunate coincidences, the farmer who found the mysterious stone is murdered, and the stone itself is stolen on the day ...